OPTIMIZATION OF THE INTERNATIONAL ECONOMIC SYSTEM IN THE CONDITIONS OF QUOTATION ON THE DOMESTIC MARKET (INNOVATIVE ECONOMY, 2020)
Shpak N.H. OPTIMIZATION OF THE INTERNATIONAL ECONOMIC SYSTEM IN THE CONDITIONS OF QUOTATION ON THE DOMESTIC MARKETPurpose. The aim of the article is to investigate the effect of establishing a quota for saturation of the domestic market on optimal volumes of production and the value of prices in the international economic system.Methodology of research. The method of mathematical modelling was used in the course of the research, which can be considered as a means of studying the real system by replacing it with a more convenient system for the experimental study (model) that retains the essential features of the original. In the simulation, the approximation of the description function was simpler and more convenient for practical analysis by the function – model.Findings. It is established that when using a strict quota on the saturation of the domestic market, the cost of domestic producer production becomes less influential, that is, it does not affect the optimum supply of products of domestic or foreign manufacturer. And this means that by setting a rigid quota, the state does not stimulate domestic producers to reduce the cost of their products. It is determined that a domestic producer will be uncompetitive in its market, if the state establishes low quota sizes, or low rates of customs duty for a foreign manufacturer, whose production has a low cost. In this case, the entire volume of the quota will be provided only at the expense of foreign producer’s products.Originality. It is substantiated that, in contrast to the existing restriction on the export of goods by quota, it is more appropriate to introduce a quota for saturation of the domestic market, since the forced liberalization of foreign economic activity can lead to significant losses as a result of uncontrolled export of goods and natural resources.Practical value. The obtained research results are the basis for using non-tariff regulation methods in the implementation of foreign economic activity.Key words: non-tariff regulation; quotation; customs clearance; domestic producer; sales market; competitiveness; duty; profit.
Keywords: Key words; non-tariff regulation; quotation; customs clearance; domestic producer; sales market; competitiveness; duty; profit.